KARAKTERISTIK ENDAPAN TIMAH SEKUNDER DAERAH KELAYANG DAN SEKITARNYA KEBUPATEN BANGKA BARAT - Mardiah Mardiah (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2013)
Research site is located in Kelayang and surrounding areas, Bangka Barat Regency, Province of Bangka Belitung. Research location largely entered into PT. Timah, Tbk Contract of Work. Geographically, this area lies in 535000 – 555000 mE and 9815000 – 9835000 mN, 48S zone,with total area is approximately 400 km, consists ofland and offshore. The rock type composed of granite rock units (Late Triassic – Early Jura) and alluvial unit (Quarter) with landform units is eroded hills, alluvial plain, and fluvial. Based on the interpretation of shallow seismic data showed basin and borehole data, the study area were filled by alluvial deposits, suspected contains tin minerals bearing. The correlation from some borehole sindicates that cassiteritemineral content in an economical quantity especially at drillholes on valley mainly in the marine (offshore). The cassiterite mineralis closely associated with the presence of the valley as a place to accumulate. Based on the drilling data which is for correlation, interpreted that there are 2 layers of sediment that contain of secondary tin depositis kaksa layer above the bedrock, and mincan layer as reworking of the kaksa layer found in finesand to clayey layer.